(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Technical analysis is an assessment of the behavior of the international currency market over a period of time. Due to the unpredictability of the dynamics of the international currency market and the possibility of losses from the conducted transactions, the study of technical means becomes of particular importance and relevance. It is the comparative analysis that identifies the advantages and disadvantages of each of the methods in order to further formulate the most profitable trading strategy. The purpose of the article is a comparative analysis of the technical analysis methods used by analysts in today’s international currency market; comparing the selected instruments of each method and determining the most effective ones. Results. Within the framework of this study three main methods of technical analysis of the international currency market were considered: graphic, method of mathematical approximation and theory of economic cycles. The individual instruments of each of the methods, such as «Japanese candlestick», simple moving average, the moving average convergence divergence (MACD), MACD histogram, Elliott waves, Fibonacci retracement levels are reviewed. A comparative analysis of the selected instruments is carried out on the basis of research of the specificity of each of them. Examples of graphs, indicators and histograms are given. It is identified that the main differences are the complexity of use (ie the use of mathematical computing and computer technology) and the type of strategy (short or long term). Common features of methods of technical analysis of the currency market are: the purpose of the analysis, the object of analysis and the influence of the factor «psychology of people». Conclusions. It is revealed that one can obtain the most accurate results in predicting the dynamics of currency quotations only by combining several methods simultaneously. Knowing the strengths and weaknesses of different technical analysis tools, you can use them to validate each other’s signals. As a result of such tactics, the analyst will get more accurate indicators that will bring him a profit. The prospect of the research is to find the best strategic schemes using a wide range of technical tools for international currency market analysis.